Virtual tour to Bracara Augusta - Bernardes, Paulo (2012)
The project »Virtual Tour to Bracara Augusta« aimed at conveying some of the archaeological records to non-specialist users by applying multimedia technology and adequate visualization paradigms and tries to create a maximum level of information expressiveness.